Synthesis of Crosslinked Block Copolymer Microparticles in Supercritical CO2 - Kartini, Alias (2023)
To this end, this work aims to develop a synthesis route to structured cross-linked BCP microparticles, with different size and morphology, by RAFT-dispersion polymerisation in scCO2. It is also essential that the developed method can preserve the microparticulate and internal nanostructure integrity, particularly in solvated environment. This study, which focuses on poly(methyl methacrylate)-block-poly(4-vinyl pyridine) (PMMA-b-P4VP) BCP with spherical (SPH) and lamellar (LAM) morphology, has been successful in crosslinking the BCP with divinyl benzene (DVB), ranging from 0 to 16 wt.%. The microparticle structure and the internal morphology is maintained by delaying the addition of the crosslinker and a portion of the second monomer. As a result polymerisation induced microphase separation within the microparticles is well maintained while the growing chains of the precursor PMMA-b-P4VP microparticles are crosslinked. The internal structures formed in the synthesised products were fully characterised by multiple instrumental techniques and promising results were revealed. The swelling and solubility behaviour of the crosslinked microparticles exhibiting either SPH or LAM internal morpholody was investigated via microscopy techniques including Tilt-TEM tomography and nitrogen adsorption isotherm. The maximum resistance point to swelling for both the SPH and LAM BCP microparticles were determined. The SPH microparticles incorporating different levels of crosslinking were found to have control over the porosity formation when swollen in ethanol. Macropores greater than 100 nm, mesopores 20 nm, sub-10 nm pores, and finally non-porous structures were all obtained by increasing the DVB concentration from 0 to 0.5, 1, and 4 wt.%, respectively. It was demonstrated that the size and porosity of the microparticle BCP can be controlled through in-situ crosslinking copolymerisation by RAFT-dispersion in scCO2. This control allows for tuning of the materials for different applications. Both the non-porous SPH (synthesised using 2.5 wt.% PDMS-MA) and the LAM particles demonstrated good potential as an enzyme support, by recording an immobilisation yield of more than 50 % during lipase immobilisation. Amongst the tested samples, the porous particles synthesised with 5 wt.% PDMS-MA and 1 wt.% crosslinker recorded the highest adsorption yield of usnic acid (79%). The extraction capacity of the majority of the microparticles synthesis using 2.5 wt.% PDMS-MA and DVB concentration ranging from 0-4 wt.% was found satisfactory for polymer stationary phase application, with the percentage of recovery meeting the estimated specification (35 to 75 %).